Synthesis of novel dual target inhibitors of PARP and EGFR and their antitumor activities in triple negative breast cancers. (1st May 2022) - Lin, Shanshan; Zhang, Xiao; Yu, Zelei; Huang, Xiuwang; Xu, Jianhua; Liu, Yang; Wu, Lixian
Graphical abstract: Abstract: The therapeutic strategy of poly (ADP-ribose) polymerase (PARP) inhibition of BRCA1/2 mutant cancers has been overwhelmingly successful, however, the highly aggressive triple negative breast cancers (TNBC) that receptor protein tyrosine kinase (RTKs) is known to be overexpressed are not sensitive to PARP inhibitors. Our research focused on exploring PARP inhibitors incorporating a bicyclic tetrahydropyridine pyrimidine. All synthesized compounds were more potent than Olaparib (ola) in killing tumor cells, especially in TNBC. Furthermore, compound 7 exhibited strong inhibitory effects on PARP enzymatic activity, moreover, the expression of EGFR and phosphorylated EGFR was inhibited by compound 7. Therefore, compound 7 can effectively inhibit TNBC cells with high expression of EGFR. In addition, significant synergistic effect of anti-tumor effect of new PARP inhibitors and adriamycin was also observed.